FORMATION OF MOTIVATION FOR MOTOR ACTIVITY IN STUDENTS THROUGH APPLIED PHYSICAL TRAINING - Зюзь, Володимир; Балухтіна, Валентіна (SWorldJournal, 2025)
Conscious activity is impossible without motivation, and physical education and sports are no exception. The article considers the issue of forming students’ motivation for physical education and sports. Methods for attracting students’ attention to heal